Introduction: Subversion and resistance in Hegel: paradigms, figures, resonances - Iannelli, Francesca; Achella, Stefania (B@belonline, 2022)
How to intend the action of the concepts of resistance and subversion within and departing from Hegelian Philosophy? This introduction aims to highlight the different semantic nuances of these concepts and how they have been read and interpreted. The notions of ‘subversion’ and ‘resistance’ refer to an ideologically marked universe, and for this reason, especially during the twentieth century, they have been articulated in different ways, expressing sometimes radically opposing interpretations. The overall goal of issue 9 of B@belonline, Hegel between subversion and resistance, is to take a post-ideological look at such concepts and their unexplored potential within and from the Hegelian system.